Vasopressin-induced Ca2+ signals in human adipose-derived stem cells. Issue 2 (March 2016) - Tran, Tran Doan Ngoc; Gimble, Jeffrey M.; Cheng, Henrique
Graphical abstract: Highlights: hASCs are multipotent cells that can differentiate into many cell types. hASCs have V1a receptors and respond to AVP during adipocyte differentiation. AVP signaling increases intracellular Ca 2+ via the Gq–PLC–IP3 pathway. Both Ca 2+ influx and release from the endoplasmic reticulum are the Ca 2+ sources. AVP inhibits adipogenesis. Abstract: Intracellular Ca 2+ signals are essential for stem cell differentiation due to their ability to control signaling pathways involved in this process. Arginine vasopression (AVP) is a neurohypophyseal hormone that increases intracellular Ca 2+ concentration during adipogenesis via V1a receptors, Gq-proteins and the PLC–IP3 pathway in human adipose-derived stromal/stem cells (hASCs). These Ca 2+ signals originate through calcium release from pools within the endoplasmic reticulum and the extracellular space. AVP supplementation to the adipogenic media inhibits adipogenesis and key adipocyte marker genes. This review focuses on the intersection between AVP, Ca 2+ signals and ASC differentiation.